The Outcome of Snare Loop Catheter for Foreign Body Removal in Superior Vena Cava: An Evidence-Based Case Report - Noorsukma, Hutomo Rezky; Darwis, Patrianef (The New Ropanasuri Journal of Surgery, 2026)
Introduction. In recent years, the utilization of central venous catheters (CVC) in medical practice has become increasingly common. One of the complications associated with central venous catheterization is embolization of catheter fragments, which arefound in 1% of cases. Currently, endovascular techniques, such as snare loop catheter, have been developed for the extraction of intravascular foreign bodies. However, there is no strong evidence regarding this method. Thisliterature review aims toevaluate the efficacy and safety of snare loop catheters for foreign body removal within the superior vena cava (SVC). Method. We searched four databases, that is Cochrane, PubMed, EBSCO, and ProQuest. We only included studies relevant to our clinical question about the efficacy and safety of snare loop catheter for foreign body removal in SVC. Results. We found 24 case reports and 10 case series from our search with a total of 224 cases. The effectiveness of the snare loop in extracting intravascular foreign bodies from the 34 articles was 97.77%, and the snare loop was successful in removing foreign bodies in 218 cases. We only found 7 cases of complications after the procedure, which are supraventricular tachyarrhythmia (3 cases), hematoma (3 cases), and tricuspid regurgitation (1 case). Conclusion. The removal of foreign bodies in the superior vena cava using a snare-loop catheter is effective and relatively safe. However, further studies with a higher level of evidence are still needed